An examination of bureaucratic motivations focusing on the federal agency of the United States Environmental Protection Agency - McMahon, R (1996)
The primary aim of this thesis is to examine the question: What is it that motivates bureaucrats? This thesis tests four models of bureaucratic motivation against data obtained during interviews conducted at the headquarters of the Environmental Protection Agency in Washington DC and the field offices in Wheeling, West Virginia. Each of the models assumes that bureaucratic motivation can be explained by a characterisation of bureaucrats as rational self-interested maximisers. The four chapters in this thesis examine what is meant by motivation and rationality and assess what it is that motivates bureaucrats in the EPA. The argument in this thesis is that non-rational accounts of motivation are essential to an understanding of the motivations of EPA officials. The conclusion assesses why it is that the data in this thesis can be interpreted as supporting the argument presented in the following work.